Doctor, I am Bleeding! Acute Scrotal Bleeding in a Middle-aged Man - Nor Azam Kamaruzaman; Siti Shahirah Nadiah Ibrahim (Asian Journal of Medicine & Health Sciences, 2024)
Acute bleeding from the scrotum is rare, and few causes exist; scrotal angiokeratoma is one of them. Angiokeratomas are violaceous skin papules that are benign and infrequent. Most individuals have asymptomatic lesions that do not need intervention, but occasionally, there may be pain, itching, and spontaneous bleeding. This is the case of a 50-year-old man who experienced abrupt and unexpected profuse scrotal bleeding